2015
DOI: 10.1557/jmr.2015.132
|View full text |Cite
|
Sign up to set email alerts
|

A review of in situ surface functionalization of gallium nitride via beaker wet chemistry

Abstract: This review focuses on in situ functionalization of gallium nitride (GaN) with different adsorbates in the presence of an etchant. The low-temperature aqueous nature of this process provides a safe, environmentally friendly technique for tailoring the semiconductor's properties for various applications. Surface binding to GaN relies on a native oxide layer or direct attachment to the metal center present on the etched surface. The specifics of the binding mechanism are based on the functional groups present on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…[35] In particular, the PA can interact with the underlying AlO x layer via POAl bonding in mono-, bi-, or tridentate modes, depending on the number of PA functional groups that are involved, as indicated in Figure 4d. [30] Previously, bidentate bonding was reported to be dominant for GaN following functionalization at elevated temperature, [36] while a range of different binding motifs has been reported for aluminum oxide surfaces. [35] To probe the binding motif and quantify the molecular coverage, XPS measurements were performed on functionalized surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…[35] In particular, the PA can interact with the underlying AlO x layer via POAl bonding in mono-, bi-, or tridentate modes, depending on the number of PA functional groups that are involved, as indicated in Figure 4d. [30] Previously, bidentate bonding was reported to be dominant for GaN following functionalization at elevated temperature, [36] while a range of different binding motifs has been reported for aluminum oxide surfaces. [35] To probe the binding motif and quantify the molecular coverage, XPS measurements were performed on functionalized surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…All phosphonic acid adsorbates, phosphoric acid, H 2 O 2 (30%), PC12 cells, and cell culture assay reagents were purchased from Sigma‐Aldrich and used as received. The surface functionalization and characterization was performed using an in situ procedure recently reviewed in the literature . The seventh passage of PC12 cells were utilized in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The surrounding areas, N polar, are considerably rougher with rms values of 37.0 ± 2.6 nm. We altered the surface chemistry of the patterned GaN using a straight forward in situ functionalization with phosphonic acid adsorbates . During the modification procedure the surface is etched with phosphoric acid and simultaneously modified via the attachment of phosphonic acid groups to the surface.…”
mentioning
confidence: 99%
“…The role of surface properties for biointerface applications has been widely studied for biomedical applications such as cell-instructive surfaces, neural interfaces, and in vitro sensing applications. Although relatively less explored, understanding the interactions of microbes at semiconductor surfaces is important for bioelectronics applications. TiO 2 and ZnO have been studied with a particular focus on the influence of nanostructures and photocatalytic properties on modulating microbial interactions for antimicrobial and biosensor applications. , Although Si is common for bioelectronics applications, the biocompatibility and wide band gap properties of III-nitride materials are advantageous in comparison for applications including sensing and communication devices. , Additionally, the treatment of GaN with chemicals such as H 2 SO 4 , H 3 PO 4 , and KOH and functionalization with organic adsorbates can modify the surface properties of the substrates. We have reported on the topography and surface chemistry modifications of GaN and Al x Ga 1– x N using wet chemical etching and functionalization with organic adsorbates. ,, Additionally, GaN exhibits persistent photoconductivity (PPC) which is the slow decay of surface charge that accumulated under UV light exposure after the light stimulus is removed. We have demonstrated that surface charge remains for several minutes after the light is removed which enabled the noninvasive stimulation of bacteria, yeast, and neurotypical cells at the interface. , The influence of surface charge has also been demonstrated by others to be an important surface property for modulating microbial interactions at interfaces. …”
Section: Introductionmentioning
confidence: 99%